THE ACADEMIC PERFORMANCE AND WELL-BEING OF UNDERGRADUATE STUDENTS; A CROSS-SECTIONAL STUDY.: http://doi.org/10.46536/jpumhs/2023/13.03.453 - Ziaullah1 , Aziz ur Rehman2 , Muhammad Ishaq3 , Nazia shuaib4 , Sheraz khan5 , Javed Iqbal6 , Amir Sultan7 , Umema Mumtaz 8 , Adnan Yousef9 ., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
BACKGROUND: Nursing students are expected to live a healthy lifestyle and have a high quality of life because they are responsible for caring for patients and resolving many of their problems. The study's goal was to assess undergraduate students' well-being and academic achievement, as well as their relationships with one another. METHOD AND MATERIALS: From December 2022 to February 2023, an analytical cross-sectional study with 379 students was undertaken in the ten nursing colleges in Khyber Pukhtankhwa using stratified sampling. Data was acquired using a student well-being questionnaire and student performance via GPA. Descriptive statistics for categorical variables were examined using frequency and percentage, while continuous variables were examined using mean and standard deviation. Chi-square test was applied to identify relationship between well-being and academic performance through SPSS 23.0. RESULTS: The total number of participants in the study was 387, with male participants outnumbering female participants 73%. The academic performance of the majority of the students was best 48.5%, followed by average performers 42.7%, and poor 8.7%. In the best category, students of the fourth semester performed well 14.5% compared to other semester students. The overall well-being of the students was best. In the well-being category the positive academic self-concept has the maximum mean score 3.71 ± 0.84, followed by the positive attitude towards the school 3.70 ± 0.95, and enjoyment in the school 3.67 ± 0.80. The study reveals that well-being is significant relationship 0.000 with academic performance.CONCLUSION: That study concluded that for achieving the best academic performance the student’s well-being is required to be good, but factors like high expectation of parents and school or fear of students in failing to achieve good grades affect their well-being.